Mediation Analysis of Satisfaction on Consumer Loyalty of Branded Smartphones in Batam City - Joy Happy Jones; Fitriana Aidnilla Sinambela (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose and purpose of conducting this research is so that researchers and umkm can understand the effect of product quality, brand trust, brand image, perceived value and price on purchasing decisions and loyalty of branded smartphone consumers in Batam City and formulate managerial implications that are applied. The type of research used is a type of survey research based on the results of the questionnaire. This research uses quantitative methods. Based on the results of the study, it was found that there was a significant influence between service quality, brand trust, the price offered, and brand image on customer satisfaction. Then it was found that there was a significant influence between product quality on consumer loyalty mediated by customer satisfaction. It was also found that there was a significant influence between the satisfaction felt by consumers and the loyalty or loyalty given by consumers. And it was found that there was a significant influence between product quality, service quality, brand trust, price, and brand image on loyalty.